2005
DOI: 10.1149/1.1856988
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Exchange Current for Hydrogen Evolution

Abstract: A density functional theory database of hydrogen chemisorption energies on close packed surfaces of a number of transition and noble metals is presented. The bond energies are used to understand the trends in the exchange current for hydrogen evolution. A volcano curve is obtained when measured exchange currents are plotted as a function of the calculated hydrogen adsorption energies and a simple kinetic model is developed to understand the origin of the volcano. The volcano curve is also consistent with Pt be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

186
3,929
2
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 4,688 publications
(4,138 citation statements)
references
References 12 publications
186
3,929
2
21
Order By: Relevance
“…25 According to the model, the formation of OH* is down hill in free energy for potentials above 0.79 V. This value is not trivially compared to voltammograms on Pt(111). The theoretical value denotes the potential at which reaction 5 is in equilibrium, this means that it should be compared with the reversible potential from the voltammogram.…”
Section: Resultsmentioning
confidence: 94%
“…25 According to the model, the formation of OH* is down hill in free energy for potentials above 0.79 V. This value is not trivially compared to voltammograms on Pt(111). The theoretical value denotes the potential at which reaction 5 is in equilibrium, this means that it should be compared with the reversible potential from the voltammogram.…”
Section: Resultsmentioning
confidence: 94%
“…The simple kinetic model proposed by Norskov and co-workers to explain the origin of the volcano plot is shown as the solid lines. 15 The volcano plot reflects the Sabatier principle. Metals to the left of Pt bind hydrogen atoms too strongly, blocking the active site and failing to evolve hydrogen.…”
Section: Figmentioning
confidence: 96%
“…The Gibbs free energy for hydrogen adsorption (G H* ) on a metal has been proposed to be a good descriptor of the intrinsic activity of a metal for HER. [15][16][17][18] A plot of exchange current densities against G H* has a volcano shape. Pt group metals are at the summit of the volcano, having the highest activity and close to zero hydrogen absorption energy (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…[41,42] In addition, theoretical calculations have indicated that the Gibbs free energy of adsorbed atomic hydrogen for TMDCs is close to zero (+ 0.08 Vf or the MoS 2 edge), demonstrating their potentialf or H 2 evolution reaction. [43] TMDCsasp hotosensitizer for improving photocatalytic activity of TiO 2 nanostructures Considering that TiO 2 can only absorb the UV portion of solar spectrum,i ti sh ighly crucial to enhance the photocatalytic efficiencyo fT iO 2 -based photocatalysts by extending their lightharvesting window to the visible light range using TMDC nanosheets due to their relatively narrow band gap. The mechanism for photocatalytic hydrogen evolution in TMDC/TiO 2 nanocomposites can be described as follows:u pon light irradiation, the electrons are injected from the valence band of TMDC nanosheets to the conduction band, leaving behind holes in the valenceb and.…”
Section: Hydrogen Evolution Reaction On Tmdc/tio 2 Nanocompositesmentioning
confidence: 99%